“家庭共決”保障脆弱人群的倫理限度及困境: Ethical Limits and Difficulties of the Family Co-determination Model - LIU, Junrong (International Journal of Chinese & Comparative Philosophy of Medicine, 2013)
LANGUAGE NOTE | Document text in Chinese; abstract in English only. The role of the family as “the first guarantee” of vulnerable groups is extremely limited and not always effective. When disagreements arise between patients and their family members, family co-determination can do nothing to help. Respecting patients’ autonomy should be taken as the premise of family co-determination; the government and society undertake more important responsibilities in the protection of vulnerable groups. DOWNLOAD HISTORY | This article has been downloaded 52 times in Digital Commons before migrating into this platform.